Productivity growth in service industries: Has Baumol's Disease really been cured? - Jochen Hartwig (ETH Zurich, KOF Swiss Economic Institute, 2006)
Since the mid-nineties, U.S. labor productivity outgrows its European counterpart by a wide margin. Several recent studies have found that this result is brought about by relatively few service industries, where productivity growth has accelerated in the U.S., but not so in Europe. Based on this finding, TRIPLETT/BOSWORTH (2003) have asserted that Baumol's Disease, according to which imbalances in productivity growth between a progressive (manufacturing) and a nonprogressive (service) sector of the economy lead to constant expenditure shifts into the latter, has been cured - at least in the U.S. The present paper challenges this statement, showing that there is only one genuine service industry with a lasting increase in productivity, namely wholesale and retailtrade. Labor productivity in the U.S. retail industry has grown fast due to a recent proliferation of Wal-Mart-type big box stores that would be practically impossible in Europe because of stricter zoning plans. Since this Wal-Mart effect is likely to taper off sooner or later, it is more accurate to say that Baumol's Disease has been protracted than to say that it has been cured.
Keywords: C82; L80; L81; O41; O47; O57; 330; Productivity; services sector; Baumol's Disease; statistical artifacts